Firms, institutions and foreign policy: the political economy of Brazilian multinationals - Rodrigues, Pietro Carlos de Souza (2018)
This thesis explores the relations between foreign policy and the internationalization of Brazilian firms. The main argument is that, since the 2000s, Brazil has benefited from the activities of national companies abroad to project itself internationally. In addition, foreign policy has been an intermediary instrument to foster business opportunities and to protect Brazilian multinationals against political risks. Our argument begins by recovering the relationship between state and business in Brazil and the way companies were considered not only on its connections with governmental institutions, but also as part of the development policies since the 1930s. We analyze how Brazilian multinationals became a central agent of Brazil\'s international political strategy and what are the consequences on the internationalization strategies. To measure the international involvement of countries, we developed the Foreign Policy Index, a tool that allowed us to evaluate some of the most important interpretations of changes in Brazil\'s foreign policy between 1998 and 2014. This index consists in information about the convergence in diplomatic positions, participation in international cooperation projects, among other data depicting countries\' foreign policy activities. With this, it was possible to demonstrate the relevance of domestic and systemic political factors to changes in the orientation of foreign policy. Finally, we argue that foreign policy should be considered in the international business literature in order to better understand business decisions while internationalizing. Exploring the Brazilian case, we found evidence that foreign policy played an important role in locational decisions of Brazilian outward direct investments.